Off-Patent Biological and Biosimilar Medicines in Belgium: A Market Landscape Analysis - Vandenplas, Yannick; Simoens, Steven; Van Wilder, Philippe; Vulto, Arnold G.; Huys, Isabelle (Frontiers in Pharmacology, 2021)
Background and objective: Best-value biological medicines may generate competition in the off-patent biologicals market, resulting in having more resources available to provide patients with access to necessary medicines while maintaining high-quality care. Belgium is a country known to have low biosimilar market shares, suggesting a malfunctioning market for off-patent biologicals. This study aims to gain an in-depth understanding of the Belgian off-patent biologicals market, by looking at the evolution in volumes and costs of the relevant products in the market. Methods: This study included a combination of quantitative and qualitative research methods. The quantitative part of this study consisted of the analysis of market data obtained by the National Institute for Health and Disability Insurance (NIHDI) for all relevant products in the Belgian off-patent biologicals market (i.e. TNF-inhibitors, insulins, granulocyte colony-stimulating factors, epoetins, rituximab, trastuzumab). In addition, for the qualitative part of this study, semi-structured interviews with Belgian stakeholders were conducted between December 2019 and March 2020. Results: Belgian market data and stakeholder perceptions suggest a suboptimal market environment for off-patent biological and biosimilar medicines. Shifts are observed after loss of exclusivities of originator biologicals toward second-generation products or new therapeutic class products, at a higher cost and often limited added value. Moreover, cost reductions for off-patent biologicals after biosimilar market entry are mainly determined by mandatory price reductions applicable to both originator and biosimilar products, and not by lower prices induced by competition. For products used in the retail setting, significant mandatory price reductions for both originator and reference products with low biosimilar volumes were pointed out as the main reasons for the lack of price competition. For products dispensed in hospitals, the hospital financing system is important. First, it does not always encourage the use of lower cost alternatives. Second, competition mainly takes place at the level of confidential discounts in tenders. Most interviewees acknowledged the lack of a competitive environment, which is not supportive of a sustainable Belgian off-patent biologicals market. Conclusion: Market data and stakeholder perceptions indicate that the sustainability of the Belgian market for off-patent biologicals is challenged. A sustainable market ensures access to biological therapies now and in the future.